Fatores que dificultam o diagnóstico precoce da hanseníase em uma área endêmica no Nordeste do Brasil - Santos, Glicya Monaly Claudino dos (2023)
Introduction: Leprosy is considered a public health problem in several countries around the world, due to the high number of new cases of the disease, the morbidity and the socioeconomic impact resulting from the complications, which are often irreversible, thus compromising the quality of life of the people. people affected due to their late diagnosis. Objective: To analyze the factors that hinder the early diagnosis of individuals with leprosy in an endemic area in Northeast Brazil. Method: This is a cross-sectional study of individuals aged ≥15 years affected by leprosy. Data collection was carried out using an instrument containing demographic and clinical information, as well as factors related to late diagnosis (personnel and health services). Participants were included between November 2021 and June 2022. Simple frequencies and percentages were obtained from categorical variables. Poisson multivariate analysis was used to determine the association between the outcome variable (delay in months) and categorical variables. The research was approved by the Ethics Committee of the Federal University of Sergipe (CAAE: 47713121.9.0000.5546). Results: One hundred and twenty people affected by leprosy were included, of which 61 (50.8%) were men. Most participants were between 40 and 49 years old, 74 (61.8%) self-declared as mixed-race, 91 (75.8%) lived in urban areas and 55 (45.9%) had ≤4 years of schooling. A total of 92 (76.7%) were classified with the multibacillary (MB) leprosy and 62 (52.5%) with the borderline clinic form. The median (IIQ) between the perception of signs and symptoms and seeking for a health service was 3 (1-7.5) months. The median (IIQ) between the first signs and symptoms and the definitive diagnosis of leprosy was 10.5 (4-24) months. The variables associated with delayed diagnosis were being male, increasing age, residing in an urban area, having MB leprosy, not seeking the health service after notice of the first symptoms, excessive referrals and three or more consultations for diagnostic confirmation. Conclusion: This study demonstrates that such results require educational actions aimed at people affected by leprosy and the general population, aiming at information related to the signs and symptoms of leprosy, seeking to reduce the delay in the diagnosis of people affected by it. Added to this, there is a need for greater qualification of professionals on the clinical and epidemiological aspects of the disease, which can help in the implementation of control measures and health surveillance of leprosy, contributing to the prevention of disabilities and offering a better quality of care. life for people affected by leprosy.